Autophagic degradation of the inhibitory p53 isoform Δ133p53α as a regulatory mechanism for p53-mediated senescence - Horikawa, Izumi; Fujita, Kaori; Jenkins, Lisa M Miller; Hiyoshi, Yukiharu; Mondal, Abdul M; Vojtesek, Borivoj; Lane, David P; Appella, Ettore; Harris, Curtis C (Nature communications, 2014)
Δ133p53α, a p53 isoform that can inhibit full-length p53, is downregulated at replicative senescence in a manner independent of mRNA regulation and proteasome-mediated degradation. Here we demonstrate that, unlike full-length p53, Δ133p53α is degraded by autophagy during replicative senescence. Pharmacological inhibition of autophagy restores Δ133p53α expression levels in replicatively senescent fibroblasts, without affecting full-length p53. The siRNA-mediated knockdown of pro-autophagic proteins (ATG5, ATG7 and Beclin-1) also restores Δ133p53α expression. The chaperone-associated E3 ubiquitin ligase STUB1, which is known to regulate autophagy, interacts with Δ133p53α and is downregulated at replicative senescence. The siRNA knockdown of STUB1 in proliferating, early-passage fibroblasts induces the autophagic degradation of Δ133p53α and thereby induces senescence. Upon replicative senescence or STUB1 knockdown, Δ133p53α is recruited to autophagosomes, consistent with its autophagic degradation. This study reveals that STUB1 is an endogenous regulator of Δ133p53α degradation and senescence, and identifies a p53 isoform-specific protein turnover mechanism that orchestrates p53-mediated senescence.
Keywords: wortmannin; cykloheximid; ubikvitinligasy; Membrane Proteins; Humans; sekvestosom 1; stárnutí buněk; nádorový supresorový protein p53; adaptorové proteiny signální transdukční; Androstadienes; genový knockdown; lidé; Adaptor Proteins, Signal Transducing; autofagie; Cells, Cultured; Ubiquitin-Protein Ligases; Gene Knockdown Techniques; Wortmannin; RNA, Small Interfering; protein - isoformy; Protein Isoforms; Apoptosis Regulatory Proteins; beclin 1; malá interferující RNA; Cycloheximide; androstadieny; kultivované buňky; Microtubule-Associated Proteins; proteiny asociované s mikrotubuly; Sequestosome-1 Protein; proteiny regulující apoptózu; membránové proteiny; fibroblasty; Cellular Senescence; Autophagy; Beclin-1; Fibroblasts; Tumor Suppressor Protein p53